Coffee and tea consumption and mortality from all causes, cardiovascular disease and cancer: a pooled analysis of prospective studies from the Asia Cohort Consortium. (1st September 2021) - Shin, Sangah; Lee, Jung Eun; Loftfield, Erikka; Shu, Xiao-Ou; Abe, Sarah Krull; Rahman, Md Shafiur; Saito, Eiko; Islam, Md Rashedul; Tsugane, Shoichiro; Sawada, Norie; Tsuji, Ichiro; Kanemura, Seiki; et al.
Abstract: Background: Accumulating evidence suggests that consuming coffee may lower the risk of death, but evidence regarding tea consumption in Asians is limited. We examined the association between coffee and tea consumption and mortality in Asian populations. Methods: We used data from 12 prospective cohort studies including 248 050 men and 280 454 women from the Asia Cohort Consortium conducted in China, Japan, Korea and Singapore. We estimated the study-specific association of coffee, green tea and black tea consumption with mortality using Cox proportional-hazards regression models and the pooled study-specific hazard ratios (HRs) using a random-effects model. Results: In total, 94 744 deaths were identified during the follow-up, which ranged from an average of 6.5 to 22.7 years. Compared with coffee non-drinkers, men and women who drank at least five cups of coffee per day had a 24% [95% confidence interval (CI) 17%, 29%] and a 28% (95% CI 19%, 37%) lower risk of all-cause mortality, respectively. Similarly, we found inverse associations for coffee consumption with cardiovascular disease (CVD)-specific and cancer-specific mortality among both men and women. Green tea consumption was associated with lower risk of mortality from all causes, CVD and other causes but not from cancer. The association of drinking green tea with CVD-specific mortality was particularly strong, with HRs (95% CIs) of 0.79 (0.68, 0.91) for men and 0.78 (0.68, 0.90) for women who drank at least five cups per day of green tea compared with non-drinkers. The association between black tea consumption and mortality was weak, with no clear trends noted across the categories of consumption. Conclusions: In Asian populations, coffee consumption is associated with a lower risk of death overall and with lower risks of death from CVD and cancer. Green tea consumption is associated with lower risks of death from all causes and CVD.